2022
DOI: 10.1002/ps.6926
|View full text |Cite
|
Sign up to set email alerts
|

Systemic assessment of the chiral insecticide pyriproxyfen in a citrus nectar source system: Stereoselective degradation, biological effect and exposure risk

Abstract: BACKGROUND: Balancing the safety and efficiency of chiral pesticides can help protect pollinators. We evaluated the stereoselective behavior, bioactivity, toxicity and exposure risk of the chiral insecticide pyriproxyfen in a citrus nectar system. RESULTS: Density functional theory (DFT) and ultra-performance liquid chromatography tandem mass spectroscopy (UPLC-MS/ MS) were applied for absolute configuration appraisal and chiral analysis validation, respectively. The recoveries ranged from 72.3% to 100.5% with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…The crystal belonged to an orthorhombic lattice with space group P2 1 2 1 2 1 . Its unit cell parameters: a = 6.7307( 5 μ(Mo-Kα) = 0.517 mm −1 , and D calc = 1.569 g/cm 3 . The final refinement resulted in R1 of 0.0366 [I > 2σ(I)], wR2 of 0.0911 with S = 1.03.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal belonged to an orthorhombic lattice with space group P2 1 2 1 2 1 . Its unit cell parameters: a = 6.7307( 5 μ(Mo-Kα) = 0.517 mm −1 , and D calc = 1.569 g/cm 3 . The final refinement resulted in R1 of 0.0366 [I > 2σ(I)], wR2 of 0.0911 with S = 1.03.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Rint and Rsigma were measured as 0.0300 and 0.0268, respectively. The compound crystallized in an orthorhombic lattice with space group P2 1 2 1 2 1 , exhibiting unit cell parameters: a = 9.2768(5) Å, b = 6.6079(4) Å, c = 21.6333(13) Å, V = 1326.12(13) Å 3 ; Z = 4, μ(Mo-Kα) = 0.515 mm −1 , and D calc = 1.563 g/cm 3 . The final refinement yielded R1 of 0.0475 [I > 2σ(I)], wR2 of 0.1439, with S = 1.07.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, fluindapyr contains a single chiral center atom, allowing for a pair of enantiomers (Figure S1). In some organisms and environmental media, the environmental behavior, biological activity, and toxicity of chiral pesticide enantiomers may exhibit significant differences even though each enantiomer has the same physical and chemical properties. Therefore, the traditional risk evaluation for chiral pesticides based on a racemate mixture may not produce accurate results. Many studies have reported a stereoselective phenomenon of chiral fungicides in environmental media and organisms.…”
Section: Introductionmentioning
confidence: 99%